A DIDACTIC MODEL FOR THE PHYSICAL, PSYCHOLOGICAL AND SOCIAL IMPACT OF SPORT - ven Schneider, (Sport Scientific And Practical Aspects, 2025)
Due to its multifaceted effects, sport is referred to as a “polypill” and compared with pleiotropic drugs. This article summarises the biopsychosocial effects of sport. Particular attention is given to the psychological and social effects of physical activity on children and adolescents. Firstly, sport is defined according to its various forms of organization followed by a description of the individual effects on physical, psychological and social resources. These range from motor performance abilities (conditioning and coordinative abilities) as well as from cognitive, emotional and motivational aspects to social skills. Although sport – particularly regular physical exercise – can strengthen physical, psychological and social resources, it is also true that non-physiological stresses, inadequate supervision and normative structures still have the potential to induce harm at an individual level. Furthermore, socialisation and enculturation processes relevant to children and adolescents are integrated in the model. The skills learned through sport, particularly psychological and social skills, can thus become important in other areas of life too. The model proposed here can be used in both university and non-university teaching as well as for planning specific studies and training approaches